2014
DOI: 10.1126/scitranslmed.3009546
|View full text |Cite
|
Sign up to set email alerts
|

IL-32 is a molecular marker of a host defense network in human tuberculosis

Abstract: Tuberculosis is a leading cause of infectious disease–related death worldwide; however, only 10% of people infected with Mycobacterium tuberculosis develop disease. Factors that contribute to protection could prove to be promising targets for M. tuberculosis therapies. Analysis of peripheral blood gene expression profiles of active tuberculosis patients has identified correlates of risk for disease or pathogenesis. We sought to identify potential human candidate markers of host defense by studying gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
108
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 60 publications
2
108
1
1
Order By: Relevance
“…WGCNA analysis identified 17 modules of coexpressed genes ( Figure 3, y axis). To determine which modules were associated with each disease subtype, we performed module eigengene correlation of the samples clustering within the main subtype branch by coding traits as a binary matrix of zeros and ones: each sample had a value of "1" for its corresponding subtype and a value of "0" for all other subtypes (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WGCNA analysis identified 17 modules of coexpressed genes ( Figure 3, y axis). To determine which modules were associated with each disease subtype, we performed module eigengene correlation of the samples clustering within the main subtype branch by coding traits as a binary matrix of zeros and ones: each sample had a value of "1" for its corresponding subtype and a value of "0" for all other subtypes (30).…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify genes and functional pathways associated with leprosy subtypes, we performed weighted gene correlation network analysis (WGCNA) on the filtered leprosy gene expression profiles (29,30). WGCNA is a clustering approach that identifies the typical pattern of each cluster (the eigengene).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, there have been limited studies on the roles of each specific isoform. One important study links IL-32 to IL-15-induced defense response against Mycobacterium tuberculosis in macrophages (30). Interestingly, we found that skin LCs and dermal CD1a dim CD141…”
mentioning
confidence: 66%
“…IL-32g can trigger TNF-a and IL-6 production, the maturation of DCs (24), and the activation of NK cell cytotoxicity through cell death receptor 3 (44). Furthermore, IL-32g has been shown to be protective in tuberculosis (30,45,46). In contrast, little is known about the IL-32a isoform, except that it was indicated to have a regulatory function by inhibiting the production of TNF-a or IL-6 in PBMCs (25).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation